Aspectos probatórios da tutela inibitória - Carnelós, Rubens Sampaio (2020)
The aim of this dissertation is to study the evidence in prohibitory injunction. The starting point is the study of the feauture and outline of prohibitory injunctions, basing its study on the development of the concept of action and jurisdiction, emphasising, in this connection, the role of precautionary judicial protection. In this dissertation some of the criteria and values brought by the doctrine are examined in order to have procedural effectiveness, pointing out the importance and the role of the state, justice and the procedure. Furthermore, the aim is to indicate the new trends of civil responsability where there is new outlines to the legal environment of the role and concept of unlawful action and the knowledge about role of fault and damage in the prohibitory injunctions. Afterwards, any general features of the evidence can be verified, pointing out how it has ruled by the Code of Civil Procedure. Notably, the importance of adversarial principle, efficiency and justification of judicial decisions in the evidence activity. Lastly, the aim is research the way the evidence it is conceived in prohibitory injunctions, emphasising how some legal institutes like burden of proof, circumstantial evidence, maxims (or rules) of experience, valuation of evidentiary elements, evidentiary reasoning are understood in the prohibitory injunctions